The development and characterization of a nervonic-acid-rich structured lipid - Li, Guo Ying; Yang, Hao Duo; Wen, Jian Xin; Sun, Yi Xiang; Zhang, Wei Min; Tan, Chin Ping; Xu, Yong Jiang (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Nervonic acid (NA), an ultra-long-chain monounsaturated fatty acid, has attracted widespread attention in recent years due to its notable neuroprotective and antioxidant effects. In this study, a structured lipid was developed by enzymatically interesterifying coconut oil, palm stearin, and NA. The effects of lipase type, reaction temperature, time, and enzyme dosage on NA incorporation were investigated. The highest NA content in the structured lipid was achieved under optimized conditions: a reaction temperature of 64.6 °C, a reaction time of 7.17 h, and an enzyme dosage of 8.46%. Subsequently, a machine learning model was constructed to predict the sliding melting point. The NA-rich structured lipid, designed and prepared for use as a plastic fat, comprised 59.34% unsaturated fatty acids (46.76% NA) and exhibited β’ crystal polymorphism. This combined experimental and computational approach is a reliable strategy for preparing functional structured lipids.